234k views
5 votes
Given that a = -1, b=2 and c= -3 ,find the value of a(b2+c2)

User Ariane
by
4.3k points

1 Answer

2 votes

Answer:

a(
b^(2)+
c^(2)) = = -13

Explanation:

Given that a = -1, b=2 and c= -3

find the value of a(
b^(2)+
c^(2))

Just substitute the values given for each variable

a(
b^(2)+
c^(2)) = (-1)(
2^(2)+
(-3)^(2)) ; do the exponents first

a(
b^(2)+
c^(2)) = (-1)(4+9)=(-1)(13) ; now add inside the parenthesis;

a(
b^(2)+
c^(2)) = -13 ; and multiply by -1

User Rxmnnxfpvg
by
4.6k points